Potencial farmacológico do composto triterpênico 29- hidrofriedelan-3-ona isolado do galho de maytenus gonoclada mart. (maytenus robusta reissek) na resposta imune inata e hiperalgesia mecânica induzidas por LPS - Leonardo Augusto de Melo (2023)
The present work focuses on exploring the pharmacological potential of the compound 29-hydroxyfriedelan-3-one (29-HF), isolated from the branches of Maytenus gonoclada Mart., in relation to experimentally induced innate immune response and mechanical hyperalgesia by LPS administration in the lungs and paws of mice, respectively. To investigate the effects of pre-treatment with 29-HF, administered subcutaneously, on the LPS response, we collected bronchoalveolar lavage and assessed the recruitment of white blood cells in this space, along with the release of cytokines IL-6, IL-1β, and TNF-α, along with myeloperoxidase activity. Furthermore, to evaluate the analgesic potential of 29-HF in relation to inflammation-induced mechanical hyperalgesia in response to intraplantar LPS injection, we conducted the modified Randall-Selitto test in mice. The results demonstrated that pre-treatment with 29-HF exhibited significant anti-inflammatory effects in a model of acute pulmonary inflammation induced by intranasal LPS instillation. This was manifested by a significant reduction in neutrophil recruitment into the bronchoalveolar space, as well as a reduction in the release of IL-1β and IL-6 in this model. Additionally, 29-HF also showed efficacy in reducing myeloperoxidase activity in the bronchoalveolar lavage. In the model of mechanical hyperalgesia induced by intraplantar LPS injection, treatment with 29-HF, administered intraperitoneally and intraplantar, resulted in a significant increase in the nociceptive response threshold in animals challenged with intraplantar LPS injection. This analgesic effect of 29-HF was further confirmed in tests to assess potential neuromotor alterations on a Rotarod, where animals treated with 29-HF did not exhibit significant differences in motor performance compared to the PBS-treated group. In summary, our findings suggest that 29-HF possesses pharmacological anti-inflammatory and analgesic effects in models of acute pulmonary inflammation and LPS-induced mechanical hyperalgesia.